T=11+6

Simple and best practice solution for T=11+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for T=11+6 equation:


Simplifying
T = 11 + 6

Combine like terms: 11 + 6 = 17
T = 17

Solving
T = 17

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Simplifying
T = 17

See similar equations:

| 5(5x^2-9x+2)=0 | | (x^2)+8x+-8=0 | | 3x-10=78 | | ((20-3y)+2)+3y=22 | | x-122=49-8x | | 8t+4-2y=22 | | 2x+20=0.571428571x | | -b+4=8 | | 6x-2x=22 | | 5x-3=85-3x | | 8x-78=x+41 | | -6x+5y=-1 | | -64-4x=-12x+120 | | 2x+8=72+6x | | b-8=3b+4 | | -6=3w+6 | | (10z+45)+3(6z+7)=180 | | -16=11x-264 | | -12x^2+16=0 | | -50+9x=16+6x | | f(x)=-0.75x-1 | | 6x+y-4+x-9y+1=180 | | 5w+1=3w-3 | | m(x)=-6.5x | | 5b+1=2(b+2) | | x-48=28-3x | | 5x+5+5=14+2x | | h(x)=2.25x | | 37x+12y=22 | | (.5)(6)(x)=27 | | -35-7x=23-9x | | -95+2x=118-6x |

Equations solver categories